How do dinosaurs go to school? - Yolen, Jane.; Teague, Mark (New York : Blue Sky Press, 2007)
Explains how young dinosaurs should behave during a typical school day.
490
Keywords: Dinosaurs -- Juvenile fiction; Etiquette for children and teenagers -- Juvenile fiction; Schools -- Juvenile fiction; Stories in rhyme